A high-calorie diet exacerbates lipopolysaccharide-induced pneumonia by promoting acetate-mediated macrophage polarization via the HDAC9/10–HIF-1α–glycolysis axis - Li, Qianqian; Liu, Hui; Bai, Chen; Jiang, Lin; Su, Chen; Qin, Xueying; Liu, Tiegang; Gu, Xiaohong (Frontiers in Immunology, 2025)
Lung macrophage polarization imbalance is an important cause of aggravated pulmonary inflammation. The gut microbiota metabolites short-chain fatty acids (SCFAs) are an important regulator of macrophage polarization. A high-calorie diet has been shown to aggravate pneumonia and delay recovery, especially in children. However, the underlying mechanisms remain unclear. Our previous studies showed that a high-calorie diet can disrupt the gut microbiota structure and SCFA metabolism to aggravate LPS-induced lung inflammatory damage in juvenile rats. In this study, we investigated whether pneumonia aggravated owing to a high-calorie diet is associated with SCFA-driven macrophage phenotype changes in distal lung tissues and related mechanisms. Our data revealed that a high-calorie diet significantly aggravated pulmonary inflammatory injury in juvenile mice with LPS-induced pneumonia and also increased lung tissue M1-like (CD206-CD86+)/M2-like (CD206+CD86-) macrophage polarization imbalance. We found that a high-calorie diet decreased SCFA levels in mouse stool, serum, and lung tissues, which was most pronounced for acetate. Furthermore, we found that acetate reduction mediated by a high-calorie diet exacerbated M1-like (CD206⁻CD86⁺)/M2-like (CD206⁺CD86⁻) macrophage polarization imbalance in the lung tissue of pneumonia model mice and was associated with inhibiting histone deacetylase (HDAC), rather than G-protein-coupled receptor 43 (GPR43) signaling. More critically, we found that acetate supplementation had the most significant impact on HDAC9 and HDAC10 in the lung macrophages of pneumonia model mice fed a high-calorie diet. Furthermore, overexpression of Hdac9 and Hdac10 significantly attenuated the improvement effects of acetate on lung tissue M1-like (CD206-CD86+)/M2-like (CD206+CD86-) macrophage polarization in pneumonia model mice fed a high-calorie diet, and this mechanism was associated with the HIF-1α–glycolysis axis. Taken together, we demonstrated that a high-calorie diet could cause acetate levels to decrease in mice with LPS-induced pneumonia. This decrease in acetate was associated with a diminished inhibitory effect on HDAC9/10, potentially contributing to upregulation of HIF-1α expression and increased glycolysis. These changes may be linked to an imbalance in M1-like (CD206−CD86+)/M2-like (CD206+CD86−) macrophage polarization and aggravate lung tissue inflammatory injury. Our findings show that acetate supplementation may be a potential treatment strategy to prevent and treat pneumonia and other infectious diseases.